Aerobic Training in Children with Cerebral Palsy - Nsenga, A. L.; Shephard, R. J.; Ahmaidi, S. (International Journal of Sports Medicine, 2013)
Rehabilitation is a major goal for children with cerebral palsy, although the potential to enhance cardio-respiratory fitness in such individuals remains unclear. This study thus compared current cardio-respiratory status between children with cerebral palsy and able-bodied children, and examined the ability to enhance the cardio-respiratory fitness of children with cerebral palsy by cycle ergometer training. 10 children with cerebral palsy (Gross Motor Function Classification System levels I and II) participated in thrice-weekly 30 min cycle ergometer training sessions for 8 weeks (mean age: 14.2±1.9 yrs). 10 additional subjects with cerebral palsy (mean age: 14.2±1.8 yrs) and 10 able-bodied subjects (mean age: 14.1±2.1 yrs) served as controls, undertaking no training. All subjects undertook a progressive cycle ergometer test of cardio-respiratory fitness at the beginning and end of the 8-week period. Cardio-respiratory parameters [oxygen intake V ˙ O2), ventilation V ˙ E) and heart rate (HR)] during testing were measured by Cosmed K4 b gas analyzer. The children with cerebral palsy who engaged in aerobic training improved their peak oxygen consumption, heart rate and ventilation significantly (p<0.05) and they also showed a non-significant trend to increased peak power output. In conclusion, children with cerebral palsy can benefit significantly from cardio-respiratory training, and such training should be included in rehabilitation programs.
Keywords: children; cerebral palsy; exercise; cardio-respiratory fitness